SOCIO-HUMANITARIAN FOUNDATIONS OF PROFESSIONAL TRAINING OF SPECIALISTS TO ENSURE SUSTAINABLE DEVELOPMENT OF SOCIETY (Innovative professional education, 2024)
The significance of the phenomenon of «socio-humanitarian education» has been updated not only for ensuring quality professional training of young people and adults for the realization of a successful professional career, but also for the protection of the country’s national and economic interests, the democratic foundations of the existence of Ukrainiansociety and the achievement of its sustainable development. Socio-humanitarian education is presented as a component of the educational system of independent Ukraine, which has a decisive influence on the processes of formation and development of theindividual, nation- and state-building and is relevant to the solution of many Sustainable Development Goals. The problems and contradictions that hinder the socio-humanitarian development of Ukrainian citizens are outlined. The tasks for improving the quality ofsocio-humanitarian training of citizens of Ukraine as educated individuals, successful professionals, responsible citizens, active members of a democratic society capable of ensuring its sustainable development are defined.
Keywords: соціогуманітарна освіта, професійна підготовка молоді й дорослих, сталий розвиток суспільства